Problematika Lembaga Pendidikan Islam di Era Society 5.0 : Perspektif Digitalisasi dan Transformasi Pendidikan - Khairunnisa Khairunnisa; Junaidi Junaidi; Andy Riski Pratama (Jurnal Visi Manajemen, 2024)
This research analyzes the problems of Islamic educational institutions in facing the challenges of digitization and transformation of education in the era of Society 5.0. Using the library research method, this study examines literature related to the digitization of education, technology in Islamic education, and the application of Society 5.0 in learning. The focus of the research is to identify challenges, barriers, and opportunities for technology integration, as well as to provide strategic recommendations for improving teacher competence, curriculum adaptation, and technology utilization. The results show that Islamic education institutions face obstacles such as gaps in technology access, limited infrastructure, and lack of digital skills of teachers. However, digital transformation opens up opportunities to enrich learning methods through digital applications and the integration of religious values in technology platforms. Recommendations include digital training for teachers, infrastructure improvement and curriculum revision to be relevant to the digital era.